Determinants of Success in International Strategic Alliances: Evidence from the Global Aerospace Industry - Dussauge, Pierre; Garrette, Bernard (Journal of International Business Studies, 1995)
This paper presents the results of a study linking the performance of international joint ventures and alliances set up in the global aerospace industry to their strategic and organizational features. In a first stage, an empirically based taxonomy of the observed alliances is generated. Then, the economic performance of various types of alliances is evaluated on the basis of industry expert opinions, and the difference in performance of different alliance types is tested.